LOCAL AND TARGET LANGUAGE CULTURE PROPORTION IN ENGLISH TEXTBOOKS “ENGLISH ON SKY (EOS) 2” AND “WHEN ENGLISH RINGS A BELL (WERAB) VIII” - fikri yansyah (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2017)
This study aimed to find out the percentage, the balance proportion and the presentation of local and target language culture in English textbooks EOS 2 and WERAB VIII. The design was content analysis research with 2959 sentences and 887 pictures as the study data. The procedure of analyzing the data started by classifying the data into local or target language culture, then it coded under Byram & Morgan’s checklist (1994), while the pictures simply classified into local or target language culture. To see the balance proportion, Mann Whitney U-test was conducted. The presentation was made by drawing inferences. The result showed that the percentage for the analysis of sentences of local language culture was 11.78% and 12.24% for target language culture in EOS 2. Then, local language culture was 33.06% and 7.57% for target language culture in WERAB VIII. Under picture analysis, 19.5% was local language culture and 16.4% was target language culture in EOS 2, while, 43.2% was local language culture and 10.17% under target language culture in WERAB VIII. The results of Mann-Whiney U-test indicated EOS 2 has balance proportion and WERAB VIII did not have balance proportion. Under picture analysis, EOS 2 also has balance proportion than WERAB VIII. The presentation of culture in EOS 2 dominated under category #8 national cultural heritage (NCH) both local and target language culture, while local language culture in WERAB VIII focused on category #3 belief and behavior (BB) and category #8 national cultural heritage (NCH) for target language culture.